Moisture diffusion in cement pastes with hydrophobic agent. (14th February 2022) - Zhang, Hao; Mu, Song; Cai, Jingshun; Ma, Qi; Hong, Jinxiang; Wang, Jiawei; Du, Fengyin
Highlights: The effect of hydrophobic agent on moisture diffusion in cementitious materials is assessed experimentally. The evolution of the micro-structure of cement paste with hydrophobic agent was monitored to reveal the mechanism. The hydrodynamic model of cone type pore is proposed to analyze the hydrophobic impact. Abstract: Hydrophobic treatment of cement pastes is most effective ways to resist the penetration of water with aggressive ions to improve durability of cement-based materials. In this paper, the influence of carboxylic acid ammonium salt integral addition on hydrophobicity of cement-based materials is analyzed. The effects of carboxylic acid ammonium salt on hydrophobicity, moisture diffusion and hydration products are investigated by experimental methods. The results of water vapor sorption isotherm show that the addition of carboxylic acid ammonium salt increases the pore volume. The simplified analytical hydrodynamic model of cone type pore and Young's relationship is proposed to analyze the relation between characteristic parameters of pore and the permeability of cementitious materials. It can be concluded that the hydrophobicity results from the change of pore structure and the hydrophobic surface of cone region. These results provide the guidance to design the durability and to develop the new hydrophobic agent used in cementitious material.